2020
DOI: 10.1111/ijfs.14492
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibre‐based bilayer biopolymer films: enhancement of antioxidant activity and potential for food packaging application

Abstract: Summary This study aimed to enhance the antioxidant property of biopolymer film without the incorporation of external agents. The active bilayer film with improved antioxidant activity has been developed by electrospinning zein, a prolamine of corn as nanofibre (average diameter of 286 nm) on solvent cast chitosan film. Zein nanofibres exhibited a slight increase in antioxidant activity as compared to solvent cast zein film. But, zein nanofibre coating on chitosan films significantly improved its antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Besides, CH layers not including GSE might behave as a physical barrier, leading to reduced CV release from the layers. These results were similar to those reported by Bharathi et al [37] for CH-based bilayer films coated with zein nanofibers. On the other hand, Luis et al [36] did not find any significant increase in the DPPH scavenging activity (%) of zein/pullulan bilayer films when incorporated with isopropyl palmitate.…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…Besides, CH layers not including GSE might behave as a physical barrier, leading to reduced CV release from the layers. These results were similar to those reported by Bharathi et al [37] for CH-based bilayer films coated with zein nanofibers. On the other hand, Luis et al [36] did not find any significant increase in the DPPH scavenging activity (%) of zein/pullulan bilayer films when incorporated with isopropyl palmitate.…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…Results explained maximal oxygen absorption capacity, and thus, the potential gallic acid mixtures as effective oxygen scavengers for multilayer food packaging applications. In another study, Bharathi, Leena, Moses, and Anandharamakrishnan (2019) developed a bilayer nanofiber‐based packaging film from chitosan and zein for the storage of fresh‐cut apples. Results showed that the developed bilayer biopolymer film improved the antioxidant properties from 13% to 44%.…”
Section: Applications Of Multilayer Packaging Systems For Food Materialsmentioning
confidence: 99%
“…The function is to coordinate food and environment, and similarly create an internal condition suitable for food preservation, which can maintain food's original quality and extend the shelf life. At present, active packaging has a host of functions, such as antibacterial (Cui et al, 2016), antioxidant (Bharathi et al, 2020) absorption of bad odor (Shin et al, 2018) and so on. Its main application and mechanism in meat products are as follows:…”
Section: Practical Applicationsmentioning
confidence: 99%